Aedes Mosquito Population density of Dengue Fever Vectors in The Area of Pineleng Minahasa: Aedes Mosquito Population density of Dengue Fever Vectors in The Area of Pineleng Minahasa - Carolin Manuahe; Yermia Semuel Mokosuli; Ferny Margo Tumbel (Indonesian Biodiversity Journal, 2020)
Aedes mosquitoes have the behavior of sucking blood repeatedly (multiple bites) in one gonotrophic cycle, these mosquitoes are also very effective at transmitting the virus to humans (WHO 2004). Kawada et al. (2007) reported that the foraging activity of A. albopictus was less than 0.1 times compared to A. aegypti under laboratory conditions, this result is consistent with the tendency to bite both species in nature. The target-attack frequency (foraging activity) in A. aegypti female mosquitoes in unfed conditions is 30 times greater than that of A. albopictus mosquitoes in several laboratory treatments (Kawada, et al. 2007). Aedes sp is a deadly infectious vector between another dengue hemorrhagic fever (DHF) and chikungunya. Pineleng is a marginal/suburban area of Station 1. Recent studies have reported changes in habitat patterns of Aedes sp, especially Aedes albopictus and Aedes aegypti . The aim of this study is to characterize the population density of the Aagoan sp. Imago based on the time distribution and altitude of the sea surface. The population density characteristics of the Aedes spagoed imago captured inside and outside the room based on the time distribution in North Sulawesi. The stages of the study consisted of larvae surveying, larval extraction and analysis, and imago extraction and analysis. The results showed that the high population of Ae aegypti was at 8:00 a.m. to 10:00 p.m. in the morning and 14:00 to 16:00 p.m. in the afternoon before the afternoon. in the morning before noon and at 14:00 to 18:00 in the afternoon before evening.